A Perspective on Mature Gratitude as a Way of Coping With COVID-19 - Jans-Beken, Lilian (Frontiers in Psychology, 2021)
Aim and Method: This perspective searches presents evidence of mature gratitude as a way of coping with the threats and boundaries of COVID-19. This narrative, non-systematic review will be based on studies from the COVID-19 period in association with more general literature on the characteristics of mature gratitude related to good mental health. Results: The results from the literature suggest that a confrontation with our existential vulnerability during a pandemic is not only a crisis but also an opportunity to view our lives in a different way. Mature gratitude, as proposed in this perspective, can help us in coping with the threats and boundaries that are part of our lives due to the COVID-19 pandemic. This time of crisis gives us the opportunity to self-reflect on our current life and plans for the future and to reframe them through a positive lens which can encourage individuals to actively strengthen their psychological resilience and coping skills. Conclusion: Cultivating an attitude of mature gratitude through actions of kindness, expressing being thankful for life and God, and enjoying all the small things in life helps in coping with the current threats of COVID-19 and building lifelong resilience for the future. Knowledge about these associations can help psychologists, counselors, and coaches to support people who experience psychological issues due to the current pandemic and all crises to come.